Magnetostrictive properties of polymer-bonded Fe-Co based alloy composites - Na, SM; Suh, SJ; Shin, KH; Lee, YS; Lim, SH (AMER INST PHYSICS, 2003)
Polymer-bonded composites of a Fe-Co based alloy are fabricated and their magnetic and mechanical properties are characterized. The use of flake-type powders with a thickness of 3-5 mum, instead of conventional spherical powders, is the key to good magnetostrictive properties and this is made possible by suitable design of the alloy (Fe36Co62Ge2) and the development of a pulverization process. The composites exhibit high magnetostriction of 105 ppm measured at an applied field of 4.3 kOe (70 ppm at 1 kOe). Large compressive strength of 42 MPa is also obtained for the composites, indicating solid bonding of flake-type powders by the polymer. (C) 2003 American Institute of Physics.
Keywords: TERFENOL-D COMPOSITES